Resilience and sustainability in the activities of a higher education institution (Law and Safety, 2024)
The activities of a higher education institution in the context of achieving the UN Sustainable Development Goals are one of the important factors in ensuring economic, social and environmental security. Being educational and research centres of local communities, universities have an important impact on their residents, and with active educational activities and cooperation, this impact increases significantly. Another extremely important factor in this growth is teaching, research, educational and advisory activities and cooperation at the regional, national and international levels.The main purpose of this article is to describe the sustainable activities of a higher education institution to achieve the UN Sustainable Development Goals in the context of environmental, economic and social components in accordance with the standards assessed by international rankings of higher education institutions for sustainable development. Attention is focused on the international rankings of Times Higher Education University Impact Rankings. Additionally, the scheme of correlations between the UN Sustainable Development Goals and the basic spheres of global society and the differences between the interrelated concepts of “sustainable development” and “sustainability” are investigated.Sustainability is a harmonious combination of economic development, high social standards and a clean environment, reflecting the long-term goal of social relations, while according to UNESCO, sustainable development refers to the processes and ways of achieving it. In addition, sustainable development is mostly used as a legal term in the international regulatory framework. With regard to the basic components of sustainability (economy, environment and society), when studying their correlation with the UN Sustainable Development Goals, we can agree with the conclusion of a number of scholars that the economic component still prevails in the structure of the content of the UN Sustainable Development Goals. To a certain extent, this phenomenon is controversial, as the economy has a negative impact on the environment through industrial development. At the same time, in the absence of economic resources, it is impossible to invest in environmental restoration and environmentally sustainable management methods and means.
Keywords: sustainability; UN Sustainable Development Goals; university; activities of higher education institutions; education and science.